Value-added service provision through ICT by drug wholesalers in Japan - Tsutomu Nakamura (Netcom)
This report examines the ways in which drug wholesalers have played a role in healthcare distribution in Japan. Such merchants have reorganized their operations and provided new value-added services for customers through the use of Information and Communication Technology (ICT). In addition to performing intermediate distribution, they have also intensified logistics functions for pharmaceutical manufacturers and pharmacies. Because drug wholesalers need to meet the local needs of specific regions when introducing ICT, the technology is not implemented in all areas. The results of this survey on drug wholesalers highlight the balance between the potential for expanding geographic reach and practicing local specialization.